2021
DOI: 10.1142/s0219467822400083
|View full text |Cite
|
Sign up to set email alerts
|

HHO-Based Vector Quantization Technique for Biomedical Image Compression in Cloud Computing

Abstract: In the present digital era, the exploitation of medical technologies and massive generation of medical data using different imaging modalities, adequate storage, management, and transmission of biomedical images necessitate image compression techniques. Vector quantization (VQ) is an effective image compression approach, and the widely employed VQ technique is Linde–Buzo–Gray (LBG), which generates local optimum codebooks for image compression. The codebook construction is treated as an optimization issue solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The most significant image compression standard is JPEG and its quantization is classified into two kinds such as vector quantization (VQ) and scalar quantization (SQ). It is an inconvertible compression technique and is widely utilized in the compressing of images, which includes some loss of information [ 7 ]. The main motive of VQ is producing an optimum codeword (CW) which comprises a collection of CWs, where else an input image vector is allotted on the basis of minimal Euclidean distance.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant image compression standard is JPEG and its quantization is classified into two kinds such as vector quantization (VQ) and scalar quantization (SQ). It is an inconvertible compression technique and is widely utilized in the compressing of images, which includes some loss of information [ 7 ]. The main motive of VQ is producing an optimum codeword (CW) which comprises a collection of CWs, where else an input image vector is allotted on the basis of minimal Euclidean distance.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that the proposed method was more successful than other meta-processing methods in maintaining the quality of the reconstructed images. In the diagram in Figure (9), the PSNR index is compared with the average bitrate compression methods on average. According to the comparisons made, the PSNR index in the proposed method is 27.24.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…Image compression is important because it reduces storage space and speeds up image transmission over the network. Our motivation in this paper is to present an image compression version based on the LBG algorithm [9]. So far, optimization methods such as WOA [10], Bat algorithm [11], and Firefly algorithm [12] used to compress the images.…”
Section: Introductionmentioning
confidence: 99%
“…An effective method for compressing biomedical images using a CC platform and HHO-based LBG techniques was proposed by Satish Kumar et al [13]. The method that is provided allows for a seamless transition between the exploitation phase and the exploration phase.…”
Section: Related Workmentioning
confidence: 99%